Healthcare characteristics in the Yakut Arctic - Sleptsov, Spiridon; Romanova, Anna; Sleptsova, Snezhana; Burtseva, Tatiana (Mongolian Journal of Geography and Geoecology, 2025)
An analysis of the current healthcare issues in the Arctic zone of the Republic of Sakha (Yakutia) has been conducted based on materials from state statistics, data provided by the regional Ministry of Health, and a survey of managers of central district hospitals. The Yakut Arctic comprises 13 districts, and the entire territory occupying over 1.6 million km² is characterized by extremely specific and highly unfavorable ecological and socioeconomic conditions. According to statistical data, since the end of the last century the Yakut Arctic has experienced a negative demographic trend; between 1989 and 2023 the population decreased by nearly 2.5 times (from 146,000 to 65,000 inhabitants). One of the primary causes is the low standard of living, including dissatisfaction with the quality of received medical services. Accordingly, this paper devotes considerable attention to the issues of material and technical support for central district hospitals and the shortage of qualified personnel particularly, narrowly specialized physicians such as infectious disease specialists, psychiatrists specializing in addiction, ophthalmologists, neurologists, etc. The paper outlines the activities of the regional Ministry of Health in addressing several pressing issues, including the operation of mobile medical teams and medical aviation. Practical recommendations are proposed for improving healthcare provision and for attracting medical professionals to work in the remote areas of the republic, including through the provision of preferential conditions for the appointment of labor pensions. The authors emphasize that the organization of healthcare in the Yakut Arctic must be comprehensive, with mandatory support from federal programs and the involvement of the region’s fundamental economic sectors, primarily industry. The integration of new technologies, improvement of infrastructure, and development of programs for retaining and attracting healthcare workers are not only vital for the enhancement of the healthcare system in the Arctic zone of the Republic of Sakha (Yakutia) but also should contribute to reducing population outflow.